2019
DOI: 10.1093/esr/jcz031
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Effects of General and Vocational Education over the Life-Cycle and across Time: Accounting for Age, Period, and Cohort Effects

Abstract: A recent literature argues that the labour market returns to vocational education vary over the life cycle. Graduates with an occupation-specific educational degree have a smooth transition into the labour market but experience difficulties later in their career when their specific skills become obsolete. This life course penalty to vocational education is expected to be particularly strong in periods of rapid technological change. Existing literature has mostly studied this topic from the perspective of age e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 38 publications
2
29
1
Order By: Relevance
“…At the same time, mounting evidence supports that the positive employment effect of VET at the beginning of the work life reverses as workers age (Stenberg and Westerlund 2015; Forster et al 2016; Hampf and Woessmann 2017; Hanushek et al 2017; Forster and Bol 2018; Korber and Oesch 2019; Rözer and Bol 2019), such that older VET workers are less likely to be employed compared to their general education counterparts. Recent work has argued that the reasons for the reversal lie in the same factors that give VET workers their labor market premium in the beginning of their career.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…At the same time, mounting evidence supports that the positive employment effect of VET at the beginning of the work life reverses as workers age (Stenberg and Westerlund 2015; Forster et al 2016; Hampf and Woessmann 2017; Hanushek et al 2017; Forster and Bol 2018; Korber and Oesch 2019; Rözer and Bol 2019), such that older VET workers are less likely to be employed compared to their general education counterparts. Recent work has argued that the reasons for the reversal lie in the same factors that give VET workers their labor market premium in the beginning of their career.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Using data from the national Dutch labor force surveys, vocational education's early benefits disappear later in the career and become a small disadvantage before retirement. Rözer and Bol (2019) find that these age effects hold is not due to cohort or period effects. One of the few studies found a different pattern was by (Silliman and Virtanen 2019) for Finland.…”
Section: Theoretical Predictions About the Risky Choice Assumptionmentioning
confidence: 61%
“…By explicitly addressing such moderator effects, this study connects to the literature stream investigating the role of context-specific structural conditions in the life course development of inequalities (e.g. Dannefer, 2003;Kratz et al, 2019;Leopold and Leopold, 2018;Mirowsky and Ross, 2008;Rözer and Bol, 2019) and provides evidence concerning how educational life course inequality in life satisfaction, health satisfaction, and income satisfaction varies across cohorts.…”
Section: Educational Life Course Inequality Across Cohortsmentioning
confidence: 88%